Peningkatan peran serta masyarakat dalam upaya pencegahan dan pengobatan tuberkulosis di Sentajo Raya, Kabupaten Kuantan Singingi - Rita Endriani; Elda Nazriati; Ligat Pribadi Sembiring (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
The purpose of community service was to increase community participation in the prevention and treatment of tuberculosis (TB) through training of health cadres and the establishment of village TB posts in the working area of Sentajo Raya health centre. The activity method in the form of TB cadre training, the establishment of a Village TB Post and monitoring evaluation. The results of this activity were 30 people who had received training and were appointed as TB cadres. All TB cadres get TB module books, cadre pocketbooks and certificates. TB cadres must be able to play a role in the prevention and treatment of TB in their respective villages. The establishment of the first village TB post in the working area of Sentajo Raya Health Center was Pulau Kopung Sentajo Village. In the monitoring and evaluation activities of Pulau Kopung village Sentajo, a village TB post was formed in the